White locoweed and purple Astragalus in bloom - Gunther, Deb, photographer (Colorado State University. Libraries, 2001)
OXSE, white locoweed and purple Astragalus in bloom on SGS.
Keywords: locoweed; SGS; plants; flowers; Oxytropis; Astragalus (Plants)